Asuhan Keperawatan Pada Tn. T Keluarga Tn. T Dengan Gangguan Sistem Muskuloskeletal : Gout Arthritis Di Desa Kutayu RT 04 RW 01 Kecamatan Tonjong Kabupaten Brebes - Mar’ati Dina Muniroh; Tati Karyawati; Arisnawati Arisnawati (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Gouty arthritis is a degenerative disease caused by abnormal purine metabolism which is characterized by increased levels of uric acid in the blood (hyperuricemia). Gouty arthritis can attack men aged 30 - 50 years and is a disease inherited from previous generations, but not in women. Women can develop gouty arthritis after experiencing menopause. This is related to the presence of the hormone estrogen which plays a role in the process of regulating uric acid in the blood. Uric acid levels are said to be high, if the uric acid level in the blood is more than normal levels. The normal level of uric acid in men is 3.4 - 7.0 mg/dl while in women it is 2.4 - 5.7 mg/dl (Yulianingsih et al., 2022). The prevalence of gout arthritis in Central Java based on doctors' diagnoses in the elderly group 75 years and over was ranked first at 16.03%, then in the elderly group 65-74 years it was 13.90%, and in the elderly group 55-64 years it was 13.69 % (Access et al., 2022). Based on data from the Kutamendala Community Health Center, the prevalence of gouty arthritis in Kutayu Village reached 4.3%. The percentage of residents suffering from gouty arthritis in Kutayu Village is 15 people out of 346 elderly people (Kutamendala Health Center, 2022).